Invasive Alien Species of Terrestrial Vegetation of North-Eastern Uttar Pradesh - Sumit Srivastava; Ashish Dvivedi; Ravindra Prasad Shukla (International Journal of Forestry Research)
The vegetational landscape of north-eastern Terai region at the foot hills of Central Himalayas is a mosaic of grassland, old-field, wasteland, and forest ecosystems. Like many other parts of the country, this region is also infested with alien intruders which not only interfere with the growth and production of food crops but also exercise adverse effects on the biodiversity of native species. The present study attempts to catalogue the invasive alien species of the terrestrial vegetation of north-eastern Uttar Pradesh especially with reference to their habit, taxonomic position, and nativity. A total of 1135 plant species within 580 genera under 119 families are so far known to occur in the region. Of these, only 149 species within 100 genera under 41 families have been found to be invasive aliens as evident from their center of origin, past history, nature of aggregation, and invasion observed under field conditions. About 80% of these invaders have been introduced from neotropics. Out of 173 invasive plants across India, this region shares 149 species, out of which 66% of species have come from Tropical America, 14% from African continent, and the rest from other countries. A better planning in the form of early identification and reporting of infestation and spread of noxious weeds is needed for their control.